Dietary Diversity and Meal Frequency Practices among Infant and Young Children Aged 6–23 Months in Ethiopia: A Secondary Analysis of Ethiopian Demographic and Health Survey 2011. (24th November 2013) - Aemro, Melkam; Mesele, Molla; Birhanu, Zelalem; Atenafu, Azeb
Abstract : Background . Appropriate complementary feeding practice is essential for growth and development of children. This study aimed to assess dietary diversity and meal frequency practice of infants and young children in Ethiopia. Methods . Data collected in the Ethiopian Demographic and Health Survey (EDHS) from December 2010 to June 2011 were used for this study. Data collected were extracted, arranged, recoded, and analyzed by using SPSS version 17. A total of 2836 children aged 6–23 months were used for final analysis. Both bivariate and multivariate analysis were done to identify predictors of feeding practices. Result . Children with adequate dietary diversity score and meal frequency were 10.8% and 44.7%, respectively. Children born from the richest households showed better dietary diversity score (OR = 0.256). Number of children whose age less than five years was important predictor of dietary diversity (OR = 0.690). Mothers who had exposure to media were more likely to give adequate meal frequency to their children (OR = 0.707). Conclusion . Dietary diversity and meal frequency practices were inadequate in Ethiopia. Wealth quintile, exposure to media, and number of children were affecting feeding practices. Improving economic status, a habit of eating together, and exposure to media are important to improve infant feeding practices in Ethiopia.